Mosque-Based Economic Development Over a Decade with Bibliometric Review Analysis - Rusdi, Wahyudi; Wahyu Firmansyah; Hajrahwati Tahir (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2023)
This research aims to create a research map from studies conducted on mosque-based economic development. Using bibliometric analysis using Vosviewer. A total of 933 articles from 2013-2022 indexed by Scopus were used in this research. The results show a significant increase in the number of published research articles from 2013 to 2016. However, in the following years, from 2017 to 2022, there was a decrease in the number of research articles published. A very popular article is